A Randomized Trial to Determine the Efficacy of Dry Versus Wet Misoprostol for Termination of First Trimester Pregnancy - Mahaseth, BK; Singh, M; Rawal, S (Nepal Journal of Obstetrics and Gynaecology, 2012)
NJOG 2011 Nov-Dec; 6 (2): 20-23 DOI: http://dx.doi.org/10.3126/njog.v6i2.6751